PENGEMBANGAN BAHAN AJAR INTERAKTIF BERBASIS GOOGLE SITES UNTUK MATERI GELOMBANG STASIONER KELAS XI DI SMA NEGERI 1 MENJALIN: PENGEMBANGAN BAHAN AJAR INTERAKTIF BERBASIS GOOGLE SITES UNTUK MATERI GELOMBANG STASIONER KELAS XI DI SMA NEGERI 1 MENJALIN - milawati, milawati (Program Studi Pendidikan Fisika, Fakultas Pendidikan MIPA & Teknologi, Universitas PGRI Pontianak, 2025)
This study aims to develop interactive teaching materials based on Google Sites on stationary wave material for grade XI students of SMA Negeri 1 Menjalin. The research method used is Research and Development (R&D) with a 4D development model (Define, Design, Develop, Disseminate), which was modified to 3D due to time constraints. The research stages include: (1) Define to analyze learning problems; (2) Design to design Google Sites-based learning media equipped with PhET Colorado simulations and interactive quizzes; (3) Develop to validate and test the feasibility of learning media. Validation by material experts shows that the learning media is very feasible to use with an average percentage of 81.94%. Validation by media experts states that this learning media is feasible to use with an average percentage of 69.23%. The results of the trial to students showed a very positive response, with an average percentage of 80.24%. The results of the study concluded that this interactive teaching material based on Google Sites is effective in increasing students' understanding and interest in learning stationary wave material. With its interactive features, this media is an alternative solution to overcome the limitations of laboratory facilities in schools and create a more interesting learning experience.